Viscoelastic and Textural Characteristics of Masa and Tortilla from Extruded Corn Flours with Xanthan Gum - Platt-Lucero, Luis Carlos; Ramírez-Wong, Benjamín; Torres-Chávez, Patricia Isabel; Morales-Rosas, Ignacio (IntechOpen, 2012)
None